2013
DOI: 10.1097/ccm.0b013e31826a47de
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sedation and organ failure on continuous heart and respiratory rate variability monitoring in critically ill patients

Abstract: Interruption of sedation allows for uncovering a greater restoration of heart rate variability and respiratory rate variability in patients with low organ failure. The further reduction in respiratory variability during the elimination of sedation in patients with high multiple organ dysfunction syndrome suggests a differential response and benefit from sedation interruption, and merits further investigation. As reduced variability correlates with severity of illness, and need for sedation depends on organ fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…22,23 It has been shown that HRV decreases with sedation 24 and increases with sedation interruption. 25 There is also evidence to suggest that depressed HRV is predictive of overall outcome in the critical care unit. 26 Risk stratification in the ICU and the role of the various components of HRV analysis has also been further delineated in some detail.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 It has been shown that HRV decreases with sedation 24 and increases with sedation interruption. 25 There is also evidence to suggest that depressed HRV is predictive of overall outcome in the critical care unit. 26 Risk stratification in the ICU and the role of the various components of HRV analysis has also been further delineated in some detail.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that conditions such as sepsis, anoxic brain injury, and multiple organ dysfunction syndrome strongly influence autonomic function (3438). Similarly, previous work has shown that the modulation of HRV by depth of sedation is reduced in the setting of severe organ system dysfunction (8). It is thus likely that the nature and severity of underlying medical illness will need to be accounted for to optimize HRV-based sedation monitoring accuracy.…”
Section: Discussionmentioning
confidence: 54%
“…Previous pilot studies have suggested that some HRV features show systematic, drug-specific responses to anesthetic drugs (6, 7). Recently it was shown that sedation reduces heart rate and respiratory variability in patients without severe organ failure (8). …”
Section: Introductionmentioning
confidence: 99%
“…Intuitively, we suspect that these signals, if appropriately deconstructed, could provide real-time information about patient status and the need for and efficacy of interventions far beyond what could be extracted from observation of the signals or their trends (1). There are multiple studies, including the one reported in this issue of Critical Care Medicine (2), that support this possibility, but the clinical feasibility and benefit of doing so have not yet been conclusively demonstrated. One limitation is that simple plug-and-play technology that could permit anyone with normal computer skills to start archiving and analyzing data from all patients in a given ICU without a massive effort to provide coordination and technical support has yet to be developed, and even if it had been, there is no consensus on what to do with the data.…”
mentioning
confidence: 88%